Mechanical Design and Analysis of Eco-Print Textile Pounding Machine - Reflin, Rhainna Rheizkhira; Chang, Steven Henderson; Saptaji, Kushendarsyah; Triawan, Farid (Bumi Publikasi Nusantara, 2023)
This study presents the design and analysis of an automated eco-print textile pounding machine to reduce labor intensity and preserve artistic aspects. The machine offers an efficient and cost-effective solution for businesses to meet the demand for eco-friendly textiles while maintaining control over the pounding technique. By utilizing a rotating flywheel mechanism, the device achieves approximately an average of 5 pounds with a force of 8.54 N per second. It features unique characteristics, including disassembly capability and replaceable parts for easy maintenance and longevity. The safety analysis indicates favorable safety factor values of 5.68 and 4.70 for static and dynamic loads, respectively, in the most critical part. Based on these results, it can be concluded that this product is safe and has a predicted infinite lifespan. This study serves as a valuable reference for the development of enhanced eco-print textile pounding machines.